How AI transforms language teaching: the role of a teacher in the new reality - Oliinyk, Olga (ХДАК, 2025)
The rapid integration of Artificial Intelligence (AI) into education is reshaping the ways languages are taught and learned. Over the past few years, large language models (LLMs) and adaptive AI-powered platforms have become increasingly prevalent in English as a Foreign Language (EFL) contexts. From intelligent chatbots that simulate authentic dialogue to automated writing assistants and adaptive feedback systems, AI is transforming the structure of classroom interaction. This paper explores how these tools influence pedagogical design, learner motivation, and the evolving professional identity of language teachers. It argues that teachers are no longer mere transmitters of information but designers of learning experiences, curators of digital content, and ethical mediators in a rapidly changing technological landscape.
Keywords: штучний інтелект в освіті; вивчення іноземних мов